Current issues in health economics - Slottje, Daniel Jonathan, 1957-; Tchernis, Rusty (Contributions to economic analysis ;, 2010)
Across the globe every nation wrestles with how it will pay for, provide, regulate and administer its healthcare system. Health economics is the field of economics that deals with every one of those issues and the difficult issue of allocating resources where the allocation can literally mean life or death, alleviating suffering or not. A key issue that is always mentioned, but little acted on, is the role that preventive measures play in the battle against disease and using limited healthcare resources more efficaciously. This book brings together leading researchers in the healthcare economics field presenting new research on some of these key issues such as the impact of obesity on health, childrens healthcare policies, education and health; and many more.